Mathematical modelling and experimental investigation of solar air collectors with corrugated absorbers. (January 2020) - Lin, Wenye; Ren, Haoshan; Ma, Zhenjun
Abstract: This paper presents mathematical modelling and performance evaluation of solar air collectors (SACs) with corrugated absorbers for indoor space heating. Experimental tests were first conducted based on a SAC system to understand its real-time performance. A mathematical model was then developed and validated against the experimental data. A sensitivity study was further implemented to identify the key design factors and investigate their influence on the performance of the SAC. The results showed that the modelling results agreed with the experimental data. The surface absorptance and opening angle of the corrugated absorber were the most significant design variables governing the thermal efficiency of SACs. The other significant variables included the temperature setting for the outlet air from the SAC, the depth ratio of the upper air channel to the overall size of the air space, the slope and length of the SAC, the air flow rate, and the unit area mass of the absorber. Using the opening angle of 60° and surface absorptance of 0.8 can result in an average effective thermal efficiency of 27.14%, which was comparable to that using the opening angle of 120° and the surface absorptance of 0.96. The results obtained can be used to facilitate optimal design of SACs. Highlights: A solar air collector with a corrugated absorber was experimentally tested. A mathematical model was developed and validated for performance evaluation. A sensitivity analysis was used to identify the key design parameters. A small opening angle of the corrugated absorber can enhance thermal performance.